1997
DOI: 10.1007/bf01979554
|View full text |Cite
|
Sign up to set email alerts
|

A thermochemical analysis of inhalational anesthetics

Abstract: The mechanism of the anesthetic process is of interest both to the clinician and to the pharmacologist. However, this is still an unsettled issue and a multitude of models have been proposed for the process. Noticing that most models propose either a molecular perturbation by the agents or an effect on some colligative property, we explore in this article the thermodynamical consequences of these postulations. Comparison of these with experimental findings is then made. The comparison shows the inconsistency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In that work, X-ray scattering, calorimetry, and fluorescence of the lipid probe Laurdan showed that the anesthetic located at the polar headgroup region of the bilayer and induced, as already documented [6], a concentration dependent decrease of the DPPC T m together with the progressive appearance of new phases with different spacings and ending by an interdigitated phase, below the T m . In addition, it was shown that anesthetic partition in DPPC bilayers strongly differed in the fluid and gel phases and that twice less Enflurane was needed to reach a maximal effect in the fluid phase by comparison with the gel phase.…”
Section: Introductionsupporting
confidence: 53%
“…In that work, X-ray scattering, calorimetry, and fluorescence of the lipid probe Laurdan showed that the anesthetic located at the polar headgroup region of the bilayer and induced, as already documented [6], a concentration dependent decrease of the DPPC T m together with the progressive appearance of new phases with different spacings and ending by an interdigitated phase, below the T m . In addition, it was shown that anesthetic partition in DPPC bilayers strongly differed in the fluid and gel phases and that twice less Enflurane was needed to reach a maximal effect in the fluid phase by comparison with the gel phase.…”
Section: Introductionsupporting
confidence: 53%
“…pH changes) if our thermodynamic picture is to be maintained. Further, a lowering of the temperature below the phase transition temperature (∆T more than −15 K) would lead to a complete cessation of nerve activity as found in clinical experiments [47]. Note that the chemical composition of lipids can also change in response to changes in other thermodynamic variables.…”
Section: Effects Of Ph and Saltsmentioning
confidence: 93%